GC-MS analysis and hepatoprotective activity of the n-hexane extract of Acrocarpus fraxinifolius leaves against paracetamol-induced hepatotoxicity in male albino rats - Eman A. Abd El-Ghffar; Heba A.S. El-Nashar; Omayma A. Eldahshan; Abdel Nasser B. Singab (Taylor & Francis Group, 2017)
Context: In Egypt, the burden of liver diseases is exceptionally high. Objective: To investigate the components of the n-hexane extract of Acrocarpus fraxinifolius Arn. (Leguminosae) and its hepatoprotective activity against paracetamol (APAP)-induced hepatotoxicity in rats. Material and methods: TRACE GC ultra gas chromatogaphic spectrometry was used for extract analysis. Thirty albino rats were divided into six groups (five rats in each). Group 1 was the healthy control; Groups 2 and 3 were healthy treated groups (250 and 500 mg/kg b.w. of the extract, respectively) for seven days. Group 4 was hepatotoxicity control (APAP intoxicated group). Groups 5 and 6 received APAP + extract 250 and APAP + extract 500, respectively. Results: Chromatographic analysis revealed the presence of 36 components. Major compounds were α-tocopherol (18.23%), labda-8 (20)-13-dien-15-oic acid (13.15%), lupeol (11.93%), phytol (10.95%) and squalene (7.19%). In the acute oral toxicity study, the mortality rates and behavioural signs of toxicity were zero in all groups (doses from 0 to 5 g/kg b.w. of A. fraxinifolius). LD50 was found to be greater than 5 g/kg of the extract. Only the high dose (500 mg/kg b.w.) of extract significantly alleviated the liver relative weight (4.01 ± 0.06) and biomarkers, as serum aspartate aminotransferase (62.87 ± 1.41), alanine aminotransferase (46.74 ± 1.45), alkaline phosphatase (65.96 ± 0.74), lipid profiles (180.39 ± 3.51), bilirubin profiles (2.30 ± 0.06) and hepatic lipid peroxidation (114.20 ± 2.06), and increased body weight (11.58 ± 0.20), serum protein profile (11.09 ± 0.46) and hepatic total antioxidant capacity (23.78 ± 0.66) in APAP-induced hepatotoxicity in rats. Conclusion: Our study proves the antihepatotoxic/antioxidant efficacies of A. fraxinifolius hexane extract.